A Multicenter Study of 239 Patients Aged Over 70 Years With Diffuse Large B-Cell Lymphoma in China - Yang, Chunli; Li, Qiaoer; Xie, Ke; Zhang, Yakun; Xiang, Dania; Han, Yunwei; Zou, Liqun (Frontiers in Pharmacology, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common aggressive lymphoma subtype worldwide and occurs frequently in the elderly population. However, there are limited data on the clinical profiles of patients with DLBCL over 70 years of age. Our objective was to summarize the clinical characteristics, treatment strategies and survival outcomes of this population in China. Methods: This multicenter retrospective study was conducted in China from January 2012 to July 2020 to investigate the clinical characteristics and survival outcomes. A total of 239 patients with DLBCL aged over 70 years underwent pretreatment evaluations, treatment, and follow-up at local hospitals. The primary endpoints were the progression-free survival (PFS) and the overall survival (OS) rates at 2 years. Secondary endpoints included median PFS and OS, the estimated PFS and OS rates at 5 years, and adverse events during treatment. Results: With a median follow-up of 50 months (range, 1–102 months), the 2-year PFS and OS rates were 53.0% and 65.5%, respectively. The median PFS and OS were 42.1 and 96.4 months, respectively; and the estimated 5-year PFS and OS rates were 44.7% and 56.1%, respectively. Hematological toxicities were the most common adverse effects in this study, accounting for 90.4%; and leukopenia was the most frequently observed ≥ grade 3 event. Furthermore, we found that regimens without rituximab and chemotherapy cycles < 6 were significantly associated with worse survival. Additionally, in the 70–80-year group, reduction in chemotherapy dose was associated with a significantly shorter OS, with a 2-year OS rate of 74.4% in the full dose group, compared to 67.1% for the decreased-dose group (p = 0.044). Conclusion: Our study presents the clinical profiles and survival outcomes of elderly patients with DLBCL in China. Treatment of these patients requires careful evaluation of toxicities and benefits. To this end, a prognosis model, such as comprehensive geriatric assessment, is required in clinical practice to optimally manage elderly patients with DLBCL.